PENGEMBANGAN BAHAN AJAR BERBASIS MODUL MATA PELAJARAN IPS MATERI JENIS – JENIS PEKERJAAN PADA SISWA KELAS III SD INPRES KOTING KECAMATAN KOTING KABUPATEN SIKKA TAHUN AJARAN 2017/2018 - EL Puang, Desi Maria; Nahak, Yasintha Luruk (EDUTECH CONSULTANT, 2018)
This Development Research aims to develop learning materials based modules. The method of this research is the research and development by s. Thiagarajan, Dorothy s. Semmel, and Melvyn i. Semmel. This study uses several stages, namely (1) the stage of pendefenisian, (2) design phase, the development phase (3), (4) stages of deployment. Feasibility of learning materials based on the validation of the product undertaken by expert design (Lecturer) and one classroom teacher. The data type that is used is the type of qualitative and quantitative data. The data in the form of the results of the assessment regarding product quality and suggestions for revising the product, which further analyzed in dekskriptif. The results showed that the product Materials developed viable for use in learning. This is indicated by: (1) expert assessment of design (Lecturer) shows the score on learning with an average of 4.45 by category